2014
DOI: 10.1016/j.echo.2013.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Mechanics Using a Novel Comprehensive Three-View Echocardiographic Strain Analysis in a Normal Population

Abstract: Background While quantitative RV strain analysis may be useful in congenital and acquired heart disease populations with RV failure, a comprehensive, standardized approach is lacking. An 18 segment RV strain analysis obtained from 3 standardized RV apical echo images was used to determine the feasibility, normal values and reproducibility of the method in normal adults. Methods Forty healthy, prospectively-enrolled volunteers with no cardiac history and normal QRS duration received an echo optimized for stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 26 publications
1
41
0
3
Order By: Relevance
“…Certain recent studies have highlighted the opportunity to measure RV strain in an 18-segments RV strain analysis similar to the widespread LV bull's eye [26]. These authors demonstrated the utility of regional and RVLS calculated from multiple views to comprehensively assess RV function.…”
Section: Limitationsmentioning
confidence: 96%
“…Certain recent studies have highlighted the opportunity to measure RV strain in an 18-segments RV strain analysis similar to the widespread LV bull's eye [26]. These authors demonstrated the utility of regional and RVLS calculated from multiple views to comprehensively assess RV function.…”
Section: Limitationsmentioning
confidence: 96%
“…Pregnant or lactating women, athletes, and subjects addicted to alcohol were also excluded by a few authors (15,16,60), and some studies also evaluated smoking (15,21,38,82), anaemia and fever (15,16) as exclusion criteria. However, in some studies (15,19,38,43,52,54,63,82), inclusion criteria were well defined, in other sufficiently explained (20,21,24,30,50,52,61,67,70,74,76), while in few works the criteria were more generic (23,24,26,58,59,69,73).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…In the last years, normative data on new indices of STE data have become available for the LV (60,61,63,66,67), the RV (72,73), the LA (68)(69)(70)74,77,79), and the RA (70)(71)(72)(73)(74)(75)(76)(77)(78). Some of the most recent publications evaluated 3D STE parameters (61,72,95), while data on twist and untwist are still limited (60).…”
Section: Deformation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Speckle tracking image (STI) has been an alternative technique to analysis the RV strains. 6,[29][30][31][32][33][34] It depends on the assumption that the speckle pattern in the consecutive frames is preserved. 35,36 Most of the above studies use 2D echocardiography because of its high temporal resolution.…”
Section: Introductionmentioning
confidence: 99%